The Effect Of The Guided Inquiry Learning Model On The Critical Thinking Skill Of Students In Static And Dynamic Fluid Materials For Class XI MAN 2 Bukittinggi - Nelly Zamriani; Silvi Yulia Sari; Hidayati Hidayati; putri dwi sundari (PILLAR OF PHYSICS EDUCATION, 2023)
This research was conducted on the critical thinking skills of students who still need to be critical but must still be directed to develop critical thinking. One way to encourage students to think critically is to apply the guided research learning model. Applying the guided research learning model in the learning process can support critical thinking skill of students. This aims of this study is to determine the effect of the guided inquiry learning model on the critical thinking skills of class XI Natural Science students on static and dynamic fluid materials. This type of research is quasi-experimental and only has a post-trial control group. The population for this study was obtained from students of class XI Natural Science in Islamic Senior High School.  Sampling was carried out using the cluster random sampling technique. Samples were taken randomly, and Class XI natural science 1 was taken as the experimental class and Class XI natural science 3 as the control class. Data analysis was performed using a statistical t-test. The results showed that critical thinking skill of students ranged from 76.74 in the experimental class to 69.32 in the comparison class. Based on the T distribution table, obtained tbltable.04 and t count of 5.62. The condition for rejecting H0 is if the ttable < tcount. H1 is accepted because the t count value rejects H0. This confirms that applying the model of guided inquiry learning influences critical thinking skill of students in static and dynamic fluid  material.